PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN KERJASAMA DAN PRESTASI BELAJAR - Sri Fitriana (UNIB Press, 2024)
This study aims to describe the application of the Numbered Heads Together type of cooperative learning model to improve cooperation and student achievement in Civics subjects for class VIII SMP Negeri 2 Lawang Kidul Muara Enim. The research design used is classroom action research and quasi-experimental research. The research subjects were students of class VIII.B of SMP Negeri 2 Lawang Kidul in the odd semester of the 2022/2023 academic year. Through simple random sampling technique, a quasi-experimental sample was obtained, namely class VIII.G of SMP Negeri 2 Lawang Kidul as the experimental class and class VIII.F of SMP Negeri 2 Lawang Kidul Muara Enim as the control class. The instrument of this study used observation sheets and tests. The research data were analyzed by descriptive statistics, average (mean), percentage, and t-test. The results showed that the application of the Numbered Heads Together type of cooperative learning model could improve the cooperation and learning achievement of eighth grade students of SMP Negeri 2 Lawang Kidul Muara Enim